2020
DOI: 10.3389/fphar.2020.00494
|View full text |Cite
|
Sign up to set email alerts
|

Dieckol, a Major Marine Polyphenol, Enhances Non-Rapid Eye Movement Sleep in Mice via the GABAA-Benzodiazepine Receptor

Abstract: We had previously demonstrated that phlorotannins, which are marine polyphenols, enhance sleep in mice via the GABA A-benzodiazepine (BZD) receptor. Among the constituents of phlorotannin, dieckol is a major marine polyphenol from the brown alga Ecklonia cava. Although phlorotannins are known to exert hypnotic effects, the sleepenhancing effect of dieckol has not yet been determined. We evaluated the effect of dieckol on sleep-wake state of mice by analyzing electroencephalograms (EEGs) and electromyograms. Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…In general, phlorotannins enhanced the activity of GABA A -BZD receptors and increased GABA A R-mediated inward current in cells and increased the amplitude of GABA A -BZD receptors in primary cultured neurons, these effects being blocked by flumazenil. These results corroborate that phlorotannins are positive allosteric activators of GABA A -BZD receptors, which justifies their mechanism as sedative-hypnotics, such as dieckol or triphlorethol [ 138 , 139 , 140 ]. In the case of phlorotannins, there is a relevant clinical trial in which a phlorotannin supplement increased sleep duration scores vs. placebo and decreased wakefulness after sleep as well as the total wake time.…”
Section: Natural Products As Potential Gaba Modulatorssupporting
confidence: 75%
See 1 more Smart Citation
“…In general, phlorotannins enhanced the activity of GABA A -BZD receptors and increased GABA A R-mediated inward current in cells and increased the amplitude of GABA A -BZD receptors in primary cultured neurons, these effects being blocked by flumazenil. These results corroborate that phlorotannins are positive allosteric activators of GABA A -BZD receptors, which justifies their mechanism as sedative-hypnotics, such as dieckol or triphlorethol [ 138 , 139 , 140 ]. In the case of phlorotannins, there is a relevant clinical trial in which a phlorotannin supplement increased sleep duration scores vs. placebo and decreased wakefulness after sleep as well as the total wake time.…”
Section: Natural Products As Potential Gaba Modulatorssupporting
confidence: 75%
“…Dieckol was also evaluated by EEG power density, and did not affect sleep intensity, while zolpidem reduced it. Finally, the sleep-enhancing effect of dieckol and zolpidem in mice treated with zolpidem or dieckol plus flumazenil was inhibited, which confirms that dieckol exerts sleep-enhancing effects by activating the GABA A -BZD receptor [ 139 ].…”
Section: Natural Products As Potential Gaba Modulatorsmentioning
confidence: 82%
“…Our previous studies confirmed that zolpidem alters the number of bouts and sleep state transitions, similar to curcuminoids-induced sleep. 25,26 In contrast, curcuminoids increased the EEG delta activity in NREMS. This differs from sleeping pills such as benzodiazepines, which alter sleep architecture by reducing NREMS.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, they were saved as pdb format for further investigation such as molecular docking and ADMET. A preliminary dose of 1.5 mg was given, followed by 0.5 mg twice daily for the next 7 days, and then 0.5 mg once daily until the 14-day treatment was completed Secondly, the reported Ligand (L05) Dieckol (Yoon et al, 2020), (L14) Amentoflavone (Kim et al, 1998), (L17) Pectolinarin (Cheriet et al, 2020), (L18) Rhoifolin (Xiong et al, 2021) all belong to classes of flavonoid. As they are the same classes of compounds, this could be probable reason for their similar or nearly similar energy binding.…”
Section: Molecular Docking Against Sars-cov-2 Main Proteasementioning
confidence: 99%
“…Secondly, the reported Ligand (L05) Dieckol ( Yoon et al., 2020 ), (L14) Amentoflavone ( Kim et al., 1998 ), (L17) Pectolinarin ( Cheriet et al., 2020 ), (L18) Rhoifolin ( Xiong et al., 2021 ) all belong to classes of flavonoid. As they are the same classes of compounds, this could be probable reason for their similar or nearly similar energy binding.…”
Section: Computational Studiesmentioning
confidence: 99%